Faktor – Faktor Yang Berhubungan dengan Kejadian Anemia pada Ibu Hamil di Puskesmas Lubuk Buaya Padang Tahun 2015: Factors Associated with the Incidence of Anemia in Pregnant Women at Puskesmas Lubuk Buaya Padang in 2015 - Indri Ramadini; Elda Risma (NERS Jurnal Keperawatan, 2016)
Puskesmas Lubuk Buaya is the first order of Puskesmas which is the highest rate of anemia incidence in pregnant women in 2014 that is 25,1% from 22 Puskesmas in Padang city. This is due to the low level of public knowledge about anemia. The type of descriptive analytic study with cross sectional study design, the population in this study amounted to 93 people, sampling technique total sampling, so the number of samples in this study as many as 93 samples. Data collection techniques were conducted by questionnaire. Data were obtained by univariate and bivariate analysis with chi-square statistic test presented in cross-table form with 95% degree of confidence. The results of this study were (58,1%) of respondents experiencing anemia, (54,8%) respondents lack chronic energy, (51,6%) respondent have low knowledge level, (24,7) respondent have high risk parity, 54.8%) gestational distance is risky. The chi-square bivariate findings were found to have a significant relationship between nutritional status and the incidence of anemia (p = 0.004), there was a significant association between knowledge level and anemia (p = 0.018), there was a significant relationship between parity and the incidence of anemia ( P = 0.043), and there was a significant relationship between the gestational distance and the incidence of anemia (p = 0.001). Based on the results of the above analysis, suggested to health workers, especially nurses at health centers to improve counseling and services in providing information to pregnant women about anemia kejadia during pregnancy.